Intrachannel four-wave mixing in highly dispersed return-to-zero differential-phase-shift-keyed transmission with a nonsymmetric dispersion map. - Wei, X; Liu, X; Simon, S; McKinstrie, C (2006)
Nonlinear penalties due to intrachannel four-wave mixing (IFWM) in highly dispersed return-to-zero differential-phase-shift-keyed transmission are studied for both symmetric and nonsymmetric dispersion maps. As the dispersion map changes from symmetric to nonsymmetric, the nonlinear amplitude fluctuation overtakes the effect of the nonlinear phase fluctuation and dominates the system's nonlinear performance. The effect of IFWM on the bit error rate is assessed by using the semianalytical method.